Locomotive syndrome is associated with large blood pressure variability in elderly hypertensives: the Japan Ambulatory Blood Pressure Prospective (JAMP) substudy - Imaizumi, Yuki (J Clin Hypertens (Greenwich), 2016)
Chronic pain, represented by locomotive syndrome (LS), and psychosocial factors are possible factors of blood pressure (BP) variability (BPV). The authors tested the hypothesis that there are links among LS, depression, and BPV. In 85 Japanese elderly hypertensive patients with normal daily activities, the authors performed ambulatory BP monitoring, determined the LS scale (LSS), and administered the Self‐Rating Questionnaire for Depression (SRQD). The LSS score but not the SRQD score was associated with the standard deviation (SD) and coefficient of variation (CV) of daytime systolic BP (SBP) and SD of nighttime SBP (all P<.05). Higher LSS score (in quartiles) was associated with a higher SD of daytime SBP (P=.041), even after adjusting for covariates. Regarding the components of the LSS score, movement‐related difficulty and usual care difficulty were associated with the SD and CV of daytime SBP. In elderly hypertensive patients, the LSS score was associated with exaggerated systolic BPV. The LS state could be an important determinant of systolic BPV.